The Curriculum Program Productive Competence at Motorcycle Business Engineering Expertise from Teachers and DU/DI Partners - Hanif Zakwan; Sadrina Sadrina; Fathiah Fathiah; Yasni Marjaya (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
The challenges of the business and industrial worlds (DU/DI) regarding the competency of SMK graduates. One of the reasons for graduates' non-absorption in the labor market is complaints about their ability. Non-absorption of vocational graduates in the business/industrial world does not imply a lack of work prospects, but rather a lack of graduate competency. The purpose of this research ascertains the level of relevance of the curriculum for the productive program of Motorcycle Business Engineering Skills Competence at SMK Negeri 4 Banda Aceh with the needs of DU/DI, as well as to capture the competencies required by DU/DI for graduates majoring in Motorcycle Business Engineering. A quantitative descriptive method with a survey methodology is used in this investigation. This study's participants were productive teachers of TBSM competence at SMK Negeri 4 Banda Aceh and ATPM workshops that partnered with SMK Negeri 4 Banda Aceh. The Percentage descriptive statistics were employed to analyze the data. According to the findings of this study, the level of applicability of the curriculum for the productive TBSM skill competency program with the need for DU/DI is 92% on average. Initiation of the fact that the curriculum of SMK Negeri 4 Banda Aceh is really relevant.